Randomized trial of electrodynamic microneedle combined with 5% minoxidil topical solution for the treatment of Chinese male Androgenetic alopecia. (2nd January 2020) - Bao, Linlin; Gong, Lin; Guo, Menger; Liu, Taoming; Shi, Anyu; Zong, Haifeng; Xu, Xuegang; Chen, Hongduo; Gao, Xinghua; Li, Yuanhong
ABSTRACT: Background : In treating androgenetic alopecia, 5% minoxidil is a commonly used topical drug. By using electrodynamic microneedle at the same time may increase absorption of minoxidil and further stimulate hair growth. Objective : A 24-week, randomized, evaluator blinded, comparative study was performed to evaluate the efficacy of treating Chinese male androgenetic alopecia using microneedle combined with 5% minoxidil topical solution. Methods: Randomized subjects received topical 5% minoxidil (group 1, n = 20), local electrodynamic microneedle treatments (group 2, n = 20), or local electrodynamic microneedle treatments plus topical 5% minoxidil (group 3, n = 20). A total of 12 microneedle treatments were performed every 2 weeks with 2ml 5% minoxidil delivery in group three during each microneedle treatment. Patient receiving topical 5% minoxidil applied 1 ml of the solution twice daily over the course of the study. A total of 60 Chinese male subjects with Norwood-Hamilton type III-VI androgenetic alopecia were treated. Results : The mean improvement in total hair density from baseline to 24 weeks was 18.8/cm 2 in group 1, 23.4/cm 2 in group 2, and 38.3/cm 2 in group 3. The hair growth in the three groups was significantly different ( P = 0.002), but there were no significant differences in toxicity found between the three groups. Conclusions : Treatment with microneedle plus topical 5% minoxidil was associated with the best hair growth.